Cultura e integração social de refugiados no Brasil: o caso do projeto Abraço Cultural - Souza, Juliana Aparecida Borre (2018)
Refugees travel in space, but also socially, economically, politically and culturally. Those people who fear for their own lives are forced to migrate and seek protection from other countries. Those who seek Brazil as a destination try to re-signify and consolidate their ways of life. Nevertheless, they face vulnerabilities of their condition, Brazil's social inequalities and the absence of effective public policies that support them. This dissertation focuses on a civil society project, the Abraço Cultural language course that is centered on job creation for refugees through the valorization of the cultures of origin. The goal is to understand how this project works as an important actor not only in the area of employability but also for the formation of spaces of sociability and articulation of their demands.